The Role of Ecological Values in the Private Perspective in the Process of Globalization - Aktamovich, Ikramov Ravshan; Mirzayevich, Kandov Bahodir (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the role of environmental values in the worldview of the individual and their instillation in the minds of the younger generation, related to the protection of nature, the rational use of its resources. The article also analyzes the role and significance of the phenomenon of ecological outlook in the system of values in the minds of people, their groups, social communities and society as a whole. The article is scientifically substantiated by the measures taken in the country to solve global environmental problems, which in fact is a necessary factor for healthy human growth.